A posteriori error estimator based on derivative recovery for the discontinuous Galerkin method for nonlinear hyperbolic conservation laws on Cartesian grids. Issue 4 (31st March 2017) - Baccouch, Mahboub
Abstract : In this article, we develop and analyze a new recovery‐based a posteriori error estimator for the discontinuous Galerkin (DG) method for nonlinear hyperbolic conservation laws on Cartesian grids, when the upwind flux is used. We prove, under some suitable initial and boundary discretizations, that the L 2 ‐norm of the solution is of order p + 1, when tensor product polynomials of degree at most p are used. We further propose a very simple derivative recovery formula which gives a superconvergent approximation to the directional derivative. The order of convergence is showed to be p + 1 / 2 . We use our derivative recovery result to develop a robust recovery‐type a posteriori error estimator for the directional derivative approximation which is based on an enhanced recovery technique. The proposed error estimators of the recovery‐type are easy to implement, computationally simple, asymptotically exact, and are useful in adaptive computations. Finally, we show that the proposed recovery‐type a posteriori error estimates, at a fixed time, converge to the true errors in the L 2 ‐norm under mesh refinement. The order of convergence is proved to be p + 1 / 2 . Our theoretical results are valid for piecewise polynomials of degree p ≥ 1 and under the condition that each component, | f i ′ ( u ) |, i = 1, 2, of the flux function possesses a uniform positive lower bound. Several numerical examples are provided to support our theoretical results and to show the effectiveness of our recovery‐based a posteriori error estimator. © 2016 Wiley Periodicals, Inc. Numer Methods Partial Differential Eq 33: 1224–1265, 2017